Design of acoustic beam aperture modifier using gradient-index phononic crystals - Lin, Sz-Chin Steven (American Institute of Physics, 2012)
This article reports the design concept of a novel acoustic beam aperture modifier using butt-jointed gradient-index phononic crystals (GRIN PCs) consisting of steel cylinders embedded in a homogeneous epoxy background. By gradually tuning the period of a GRIN PC, the propagating direction of acoustic waves can be continuously bent to follow a sinusoidal trajectory in the structure. The aperture of an acoustic beam can therefore be shrunk or expanded through change of the gradient refractive index profiles of the butt-jointed GRIN PCs. Our computational results elucidate the effectiveness of the proposed acoustic beam aperture modifier. Such an acoustic device can be fabricated through a simple process and will be valuable in applications, such as biomedical imaging and surgery, nondestructive evaluation, communication, and acoustic absorbers.